Environmental impact study of bagasse valorization routes - Mandavgane, Sachin Arvind; Joglekar, Saurabh; Tandulje, Akshay P.; Kulkarni, Bhaskar D. (Waste and Biomass Valorization, 2018)
India is the world’s second largest sugarcane producer and a major manufacturer of molasses-derived ethanol. The sugarcane produced is widely used in the production of sugar and 1G ethanol. Though sugar and 1G ethanol are the major concerns, there is still a huge amount of bagasse waste generated in the sugar factories. This bagasse has also some end use value, as it can be utilized for production of methanol, 2G ethanol and electricity. Even though the technology for production of these value added products is well established, it is important to analyze the social, economical and environmental impacts associated with these production processes. This work compares the environmental impacts of various sugarcane conversion processes on life cycle basis. The functional unit used is one tonne of sugarcane cultivated in field. Four routes identified for bagasse conversion- conversion of bagasse to methanol (Route 1), conversion of bagasse to ethanol via 2 stage dilute acid process (Route 2), conversion of bagasse to ethanol via enzymatic process (Route 3) and electricity production from bagasse (Route 4). On comparison of these routes on midpoint indicators such as global warming potential (GWP), acidification potential (AP), eutrophication potential (EP) and ozone depletion potential (ODP) and photochemical ozone creation potential (POCP), it is observed that the methanol production is having the highest environmental indicator values. Even though ethanol production processes and cogeneration process are having nearly similar results, it can be said that cogeneration process is the more eco-friendly one.
Keywords: Bagasse valorization; Environmental impact; LCA; Midpoint indicators